Depolarization increases the apparent affinity of the Na(+)-K(+) pump to cytoplasmic Na(+) in isolated guinea-pig ventricular myocytes - Barmashenko, Gleb (Blackwell Science Inc, 1999)
1. In order to investigate the possible effect of membrane potential on cytoplasmic Na(+) binding to the Na(+)-K(+) pump, we studied Na(+)-K(+) pump current-voltage relationships in single guinea-pig ventricular myocytes whole-cell voltage clamped with pipette solutions containing various concentrations of Na(+) ([Na(+)](pip)) and either tetraethylammonium (TEA(+)) or N-methyl-D-glucamine (NMDG(+)) as the main cation. The experiments were conducted at 30 °C under conditions designed to abolish the known voltage dependence of other steps in the pump cycle, i.e. in Na(+)-free external media containing 20 mM Cs(+). 2. Na(+)-K(+) pump current (I(p)) was absent in cells dialysed with Na(+)-free pipette solutions and was almost voltage independent at 50 mM Na(+)(pip) (potential range: −100 to +40 mV). By contrast, the activation of I(p) by 0.5–5 mM Na(+)(pip) was clearly voltage sensitive and increased with depolarization, independently of the main intracellular cation species. 3. The apparent affinity of the Na(+)-K(+) pump for cytoplasmic Na(+) increased monotonically with depolarization. The [Na(+)](pip) required for half-maximal I(p) activation (K(0.5) value) amounted to 5.6 mM at −100 mV and to 2.2 mM at +40 mV. 4. The results suggest that cytoplasmic Na(+) binding and/or a subsequent partial reaction in the pump cycle prior to Na(+) release is voltage dependent. From the voltage dependence of the K(0.5) values the dielectric coefficient for intracellular Na(+) binding/translocation was calculated to be ≈0.08. The voltage-dependent mechanism might add to the activation of the cardiac Na(+)-K(+) pump during cardiac excitation.